2007
DOI: 10.1007/s00415-007-0686-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute transverse myelitis with normal brain MRI

Abstract: The majority of patients with ATM and normal brain MRI do not develop MS after 5 years of follow-up confirming the relatively low risk compared to patients with abnormal brain MRI scans. CSF is helpful in distinguishing patients more likely to develop MS. Compared to clinical attacks, serial imaging may not lead to an earlier diagnosis in ATM patients with normal brain MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…In Kira and colleagues' series of 12 patients, no relapses were documented after a mean of approximately 2 years of follow-up 5. In comparison, a recent study of patients with isolated tranverse myelitis and normal MRI brain scans suggests that the vast majority of those patients who convert to MS do so within the first 24 months 8. Further, Kira et al reported the presence of hyper-IgE-aemia to be 63% in unselected cases of unexplained monophasic myelitis compared with 18% in MS and 23% in healthy controls 5.…”
Section: Discussionmentioning
confidence: 96%
“…In Kira and colleagues' series of 12 patients, no relapses were documented after a mean of approximately 2 years of follow-up 5. In comparison, a recent study of patients with isolated tranverse myelitis and normal MRI brain scans suggests that the vast majority of those patients who convert to MS do so within the first 24 months 8. Further, Kira et al reported the presence of hyper-IgE-aemia to be 63% in unselected cases of unexplained monophasic myelitis compared with 18% in MS and 23% in healthy controls 5.…”
Section: Discussionmentioning
confidence: 96%
“…Partial myelitis, while still acute or subacute in onset, involves only a partial cross-sectional area of the spinal cord, often manifesting as asymmetric motor or sensory dysfunction, and is the more common form of myelitis observed in MS. Patients presenting with a partial myelitis have a 20-30% transition rate to clinically definite MS at 5-year follow-up, compared to only 2% of complete myelitis patients [64][65][66][67].…”
Section: Diagnosis and Risk Of Clinically Definite Msmentioning
confidence: 91%
“…4,9,22,23 For example, in the Kaiser Permanente study, females represented 71% of the cases with TM. 8 However, these studies do not control for patients who were ultimately diagnosed with MS, which has a strong female predominance.…”
Section: Discussionmentioning
confidence: 99%